Biodegradation of atrazine and ligninolytic enzyme production by basidiomycete strains - Henn, Caroline; Monteiro, Diego Alves [UNESP]; Boscolo, Mauricio [UNESP]; Da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP] (Springer Nature, 2020)
Background: Atrazine is one of the most widespread chlorinated herbicides, leaving large bulks in soils and groundwater. The biodegradation of atrazine by bacteria is well described, but many aspects of the fungal metabolism of this compound remain unclear. Thus, we investigated the toxicity and degradation of atrazine by 13 rainforest basidiomycete strains. Results: In liquid medium, Pluteus cubensis SXS320, Gloelophyllum striatum MCA7, and Agaricales MCA17 removed 30, 37, and 38%, respectively, of initial 25 mg L- 1 of the herbicide within 20 days. Deficiency of nitrogen drove atrazine degradation by Pluteus cubensis SXS320; this strain removed 30% of atrazine within 20 days in a culture medium with 2.5 mM of N, raising three metabolites; in a medium with 25 mM of N, only 21% of initial atrazine were removed after 40 days, and two metabolites appeared in culture extracts. This is the first report of such different outcomes linked to nitrogen availability during the biodegradation of atrazine by basidiomycetes. The herbicide also induced synthesis and secretion of extracellular laccases by Datronia caperata MCA5, Pycnoporus sanguineus MCA16, and Polyporus tenuiculus MCA11. Laccase levels produced by of P. tenuiculus MCA11 were 13.3-fold superior in the contaminated medium than in control; the possible role of this enzyme on atrazine biodegradation was evaluated, considering the strong induction and the removal of 13.9% of the herbicide in vivo. Although 88% of initial laccase activity remained after 6 h, no evidence of in vitro degradation was observed, even though ABTS was present as mediator. Conclusions: This study revealed a high potential for atrazine biodegradation among tropical basidiomycete strains. Further investigations, focusing on less explored ligninolytic enzymes and cell-bound mechanisms, could enlighten key aspects of the atrazine fungal metabolism and the role of the nitrogen in the process.
Keywords: Basidiomycete; Biodegradation; Co-metabolism; Fungal metabolism; Laccase; Organochlorinated; Rainforest fungi